ANALISIS SISTEM PENGENDALIAN INTERN PENGGAJIAN DAN PENGUPAHAN TERHADAP KARYAWAN PT. BUMI BELITI ABADI KABUPATEN MUSI RAWAS - Zulaika Aquarisma; Yuli Nurhayati (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aims to determine the implementation of internal control system on payroll and wages to employees of PT. Bumi Beliti Abadi Musi Rawas where the method used is qualitative. The object of research is Payroll and Wages. The result of the research is the salary system and employee salary that there is a duty between the making of payroll and payment of employee salary so often the occurrence of errors in the calculation and there is still a list of wages that are not authorized by the personnel function that can lead to fraud in the calculation of wages of employees at PT. Bumi Beliti Abadi Musi Rawas, this became an employee complaint in the payment of salary, due to errors in the calculation of employee salaries, it shows the lack of internal control in the payroll system and wages employees at PT. Bumi Beliti Abadi Musi Rawas. Keywords : Internal Control System, Payroll and Remuneration